Judith Butler y Beatriz Preciado: una comparación de dos modelos teóricos de la construcción de la identidad de género en la teoría queer. (2016)
This paper aims to contrast two theoretical models of the construction of gender identity within queer theory: the performative-stage model of Judith Butler and Beatriz Preciado´s biodrag. To meet our goal, we proceed in two steps. First, Butler´s criticism of gender metaphysics is analyzed and the central guidelines of her performative-stage model are presented. Second, the role that the concepts of pharmaco-porno-capitalism and post-Money-ism play in the work of Preciado is studied, coming then to an analysis of her biodrag model.